2003
DOI: 10.1182/blood-2002-11-3472
|View full text |Cite
|
Sign up to set email alerts
|

Immune reconstitution to cytomegalovirus after allogeneic hematopoietic stem cell transplantation: impact of host factors, drug therapy, and subclinical reactivation

Abstract: Reconstitution of cellular immunity by 3 months after hematopoietic stem cell transplantation (HSCT) is a critical determinant of the long-term success of the transplantation. We analyzed the factors affecting recovery of cytomegalovirus (CMV)-specific CD4 ؉ and CD8 ؉ function at 3 months after HSCT by univariate and multivariable analyses including source of stem cells (bone marrow vs peripheral blood stem cells [PBSCs]), age, sex, graftversus-host disease (GVHD), steroid use, conditioning regimens, ganciclov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
191
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(211 citation statements)
references
References 44 publications
17
191
1
2
Order By: Relevance
“…Both of these variables interfere with T-cell immune reconstitution, especially CMV-specific CD8 þ and CD4 þ T-cells. 36 In this respect, the increased risk of CMV-D found in univariate analysis and the high rate of progression from CMV-I to CMV-D among patients with lymphocytopenia on day þ 30 and/or þ 120 is a marker of the lack of specific anti-CMV immunity at these time points. However, multivariate analysis failed to confirm their impact, surely as we only had the absolute number of lymphocytes or CD4 þ lymphocytes, and not the anti-CMV specific lymphocyte counts.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these variables interfere with T-cell immune reconstitution, especially CMV-specific CD8 þ and CD4 þ T-cells. 36 In this respect, the increased risk of CMV-D found in univariate analysis and the high rate of progression from CMV-I to CMV-D among patients with lymphocytopenia on day þ 30 and/or þ 120 is a marker of the lack of specific anti-CMV immunity at these time points. However, multivariate analysis failed to confirm their impact, surely as we only had the absolute number of lymphocytes or CD4 þ lymphocytes, and not the anti-CMV specific lymphocyte counts.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the CMV-specific immune response is such that it has been shown to have a positive influence on the total lymphocyte count within peripheral blood, and this may be at least partly reflected in our study. 30 Lymphopenia is known to be a predictive factor for CMV reactivation after allogeneic transplantation 11,31 and may potentially be used as a surrogate marker for poor virus-specific immunity in situations where technology for ascertaining the CMV-specific immune response is not available.…”
Section: Discussionmentioning
confidence: 99%
“…9 In HSCT patients a low lymphocyte count and CD4 þ T-cell count of less than 40 per ml at 3 months post transplant have been demonstrated as risk factors for development of late CMV disease. 10 Hakki et al 11 also showed that low CD4 (o100 per ml) and CD8 (o50 per ml) T-cell counts at this time point are associated with poor CMV-specific immunity. The functional potential of the cellular immune response is also critical and dysfunctional Ag-specific CD8 þ T cells have been found as risk factors for CMV reactivation.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Despite these advances, the proper reconstitution of CMVspecific immunity is the most important factor in controlling the reactivation of the virus and in establishing longterm protection. 7 Restoration of adaptive immunity after HSCT is a slow process. Naı¨ve T-cells first appear at about 4 months after HSCT, and the full restoration of the naı¨ve T-cell pool may require 1 to 2 years.…”
Section: Introductionmentioning
confidence: 99%